Laser Metal Deposition and Wire Arc Additive Manufacturing of Materials: An Overview - R. Rumman; D.A. Lewis; J.Y. Hascoet; J.S. Quinton (Archives of Metallurgy and Materials, 2019)
Additive manufacturing (AM) is a process that joins similar or dissimilar materials into application-oriented objects in a wide range of sizes and shapes. This article presents an overview of two additive manufacturing techniques; namely Laser metal deposition (LMD) and Wire arc additive manufacturing (WAAM). In LMD, metallic powders are contained in one or more chambers, which are then channelled through deposition nozzles. A laser heats the particles to produce metallic beads, which are deposited in layers with the aid of an in-built motion system. In WAAM, a high voltage electric arc functions as the heat source, which helps with ensuring deposition of materials, while materials in wire form are used for the feedstock. This article highlights some of the strengths and challenges that are offered by both processes. As part of the authors’ original research work, Ti-6Al-4V, Stainless steel 316L and Al-12Si were prepared using LMD, while the WAAM technique was used to prepare two Al alloys; Al-5356 and CuAl8Ni2. Microstructural analysis will focus on similarity and differences in grains that are formed in layers. This article will also offer an overall comparison on how these samples compare with other materials that have been prepared using LMD and WAAM.